Intelligence and Slave Exports from Africa. (July 2020) - Asongu, Simplice A.; Kodila-Tedika, Oasis
This article examines the role of cognitive ability or intelligence on slave exports from Africa. We test a hypothesis that countries which were endowed with higher levels of cognitive ability were more likely to experience lower levels of slave exports from Africa probably due to comparatively better capacities to organize, co-operate, oversee and confront slave traders. The investigated hypothesis is valid from alternative specifications involving varying conditioning information sets. The findings are also robust to the control of outliers. JEL: I20, I29, N30